Task-Oriented Training In Rehabilitation of Gait After Stroke: Systematic Review - Vijay ghag, Dr. Shweta; Shyam ganvir, Dr. Suvarna (Journal of Medical Biomedical and Applied Sciences, 2018)
TITLE-Task-oriented training in rehabilitation after stroke: systematic review. AIM- The aim of the present study is to provide an overview of the evidence in the literature on task-oriented training to improve balance and gait of stroke survivors. BACKGROUND- Stroke is the second leading cause of death and one of the leading causes of adult disability in the Western world.One of the major purpose of the rehabilitative process it to help patients achieve as high a level of functional independence as possible within the limits of their particular impairments.Task related training (TRT) is a rehabilitation strategy that involves the practice of goal-directed, functional movements in a natural environment to help patients derive optimal control strategies for alleviating movement disorders. DATA SOURCES- A range of databases was searched to identify papers addressing taskoriented training in stroke rehabilitation, including Pubmed Papers published in English between English between April 2000 to 2015 were included. There were 5 papers in the final dataset, including. REVIEW METHOD- The selected randomized controlled trials and systematic reviews were assessed for quality. Important characteristics and outcomes were extracted and summarized. CONCLUSION- Generally, task-oriented rehabilitation after stroke has proved to be effective and relevant for stroke practice. The possible mechanism for effectiveness of task related training may be attributable to an enhancement of presynaptic inhibition of the hyperactive stretch reflexes in spastic muscles, decrease in the cocontraction of spastic antagonists, and disinhibition of descending voluntary commands to the motoneurons of paretic muscle.